Implantação do centro de convivência e cultura da rede de atenção psicossocial de Goiânia: olhares dos usuários, trabalhadores e gestor - Castro, Marla Borges de (2014)
The implantation of innovative and inventive structures as an answer to the care complexity and social inclusion has been a constant challenge to the public politics in Brazil´s Health System. The Community and Culture Centers are structures that have been receiving an outstand position in the care production, in the creation of Community spaces furtherance the citizenship exercise and in the inclusion of the people who suffer from mental disease and other vulnerable ones, making use of resources out from the sanitary and pathological areas and including the arts, culture and leisure in their daily life. In the city of Goiânia, it is in the implantation phase the first Community and Culture Center from the Psychosocial Attention Network in the Municipal Health Secretary. Taking into consideration the lack of studies about the specificities of these structures and the absence of a national regulation that guides their constitutional process, it was realized the necessity to identify elements that could be useful to form the foundation to understand these kind of structures and provide subsidies to their management. Therefore, the present survey had as its aim to investigate the implantation process of Goiânia´s Community and Culture Center through users, workers and manager´s point of view. The study, an exploratory descriptive research of a qualitative nature, was developed by an intervention process mediated by the Problematization Methodology. The data were obtained by group meetings among the participants, sustained by the 5 steps of Maguerez`s Arch and participative observation. The results were achieved after a wide discussion process, which allowed us to identify the participants conceptions about the structure, get to know how it works and its organization considering the target population, the developed practices, the structure, the team and the management; take a second thought on the collective elaboration of its implantation project besides, getting to know the Convenience Centers reality from other Brazilian regions. Yet, it was also possible to build the guidelines of this structure, which meaningfully contributed to direct its plan of action strategies. Emphasizing that the elaboration process in the guidelines of this structure was a fundamental mark to its implantation, being possible due to the dialogue and problematization process in which this study was carried out. Investigating the implantation of this structure allowed us to leave a register in its history about the inquietude and the desires that led its creation, the potentialities and the challenges that settled this process and the aspirations to guarantee its sustainability.